ABC-VEN ANALYSIS FOR OPTIMIZING CHRONIC DISEASE MEDICINE INVENTORY: A SCOPING REVIEW - Azharayesha Nurendra Deltaverona Mahardika; Muhammad Murtadho; Sutopo Patria Jati; Septo Pawelas Arso (Pena Cendekia Insani, 2026)
Chronic disease care requires stable medicine availability and efficient pharmaceutical spending. This scoping review mapped empirical evidence on the use of ABC-VEN/VED analysis for chronic disease medicine inventory optimization in health facilities. PubMed, ScienceDirect, Scopus, and Google Scholar were searched in July 2026 for full-text empirical studies published from 1 January 2021 to 30 June 2026. Screening followed PRISMA-ScR. After duplicate removal, 672 records were screened and 232 studies were included. The evidence showed that a small proportion of high-value and clinically important medicines accounted for most pharmaceutical expenditure. ABC-VEN/VED was used to support medicine planning, procurement prioritization, stock monitoring, stock-out reduction, overstock control, and waste prevention. Integrating ABC-VEN/VED into routine inventory policy may support rational pharmaceutical budgeting, improve medicine availability, and strengthen continuity of chronic disease treatment.